2014
DOI: 10.2298/bah1402215i
|View full text |Cite
|
Sign up to set email alerts
|

Survivability of lambs in relation to their dam’s haemoglobin variants

Abstract: A total of 65 Yankasa, 23 Uda and 16 Balami ewes were mated to 4 Yankasa, 3 Uda and 3 Balami rams in a diallel breeding pattern to produce 192 lambs within 9 genotypes, which were used to study survivability of lambs in relation to their dam?s haemoglobin variants. Blood samples (5ml) were collected from 104 ewes and 10 rams through jugular venepuncture. Electrophoresis was carried out in a Shandon electrophoresis tank on cellulose acetate strips. Each of the 9 lamb genotypes had very high … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 13 publications
0
2
0
Order By: Relevance
“…At the same time, the weakest links between the characteristics of wool fibers were found for HbBB hemoglobin type. IYIOLA-TUNJI et al, (2014) reported that lambs that are born to mothers with HbAB hemoglobin type had a higher survival rate compared with lambs born to ewes with two other hemoglobin types. Those authors suggested that for further reproduction should be left the individuals with HbAB hemoglobin type, because the lambs of such ewes are resistant and more vital.…”
Section: Resultsmentioning
confidence: 99%
“…At the same time, the weakest links between the characteristics of wool fibers were found for HbBB hemoglobin type. IYIOLA-TUNJI et al, (2014) reported that lambs that are born to mothers with HbAB hemoglobin type had a higher survival rate compared with lambs born to ewes with two other hemoglobin types. Those authors suggested that for further reproduction should be left the individuals with HbAB hemoglobin type, because the lambs of such ewes are resistant and more vital.…”
Section: Resultsmentioning
confidence: 99%
“…The effects of Hb BB and Hb AB on reproductive performance in sheep have been reported. Ewes carrying these types of hemoglobin have been repeatedly documented to have a better fertility than ewes with Hb AA type (Dally et al, 1980;Iyiola-Tunji et al, 2014;Važić et al, 2017).The relationship between Hb genotypes and productive traits in local sheep needs to be investigated.…”
mentioning
confidence: 99%